A Computer Programme With Temperature Gradient Capability for the Network Analysis of Hybrid Circuits. (1980) - Zimmer, Carl R.
Abstract : A modified version of the computer programme SINC-S is described which permits the user to specify independently up to 30 different device temperatures in a given problem when the proper control statement is included. An additional option is an algorithm for the steady-state solution of a non-linear network with periodic inputs, so that realistic system operation may be simulated. The programme may be used to provide more accurate simulation of circuits where large temperature gradients are present, and to furnish input data for other thermal analysis programmes